Perancangan Antena Mikrostrip Dual Band Patch Persegi Panjang dengan Slot pada Frekuensi 2,6 dan 5 GHz - Eva Yovita Dwi Utami; Nadia Permatasari Syailendra; Andreas Ardian Febrianto (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
In this study, a dual-band rectangular patch microstrip antenna with slot was designed at frequency 2.6 GHz and 5 Ghz. The antenna was simulated and realized using Duroid 5880 material with dielectric constant of 2.2 and a thickness of 1.57 mm. The rectangular antenna is designed at frequency of 2.6 GHz then frequency of 5 GHz is obtained by adding two strip slots on the patch. The simulation results show that for frequency of 2.6 GHz, VSWR value is 1.0807, reflection coefficient is -28.225 dB, gain is 7.34 dBi, and for frequency of 5 GHz, VSWR obtained is 1.0684, reflection coefficient is -29.607 dB, and gain is 7.68 dBi. Antenna is fabricated and measured. The measurement results show that for 2.6 GHz the antenna has VSWR of 1.092, reflection coefficient of -27.1 dB, and gain of 10,6 dBi. As well as the results for 5 GHz show the antenna has VSWR of 1.411, reflection coefficient of -15.3 dB, gain of 8.1 dBi and bandwidth of 124 MHz. Both simulation and measurement results show slotted dual-band rectangular patch microstrip antenna with frequency of 2.6 GHz and 5 GHz can be realized.